Hubungan Budaya Organisasi dan Kepuasan Kerja dengan Komitmen Organisasi Guru Honorer - Priarti Megawanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
The purpose of this research are to know: (1) about correlation between culture organization and commitment organization; (2) about correlation between job satisfaction and commitment organization; (3) about correlation between culture organization and job satisfaction with commitment organization. This research had done in several state elementary schools that placed on Kramatjati, East Jakarta. The method of this research is quantitative description approach. The purpose of using this method was to analyze the correlation between two or more variable through hypothesis test and also to identificate social phenomena that happened in real situation. The result of the research answering the hypothesis which are: (1) there’s a positive correlation between culture organization and commitment organization; (2) there’s a positive correlation between culture organization and commitment organization; (3) there’s significance correlation between culture organization and job satisfaction. Nevertheless, if school start to improve all of them, state elementary school will have honorary teacher with high dedication.